Immune response to SARS-CoV-2 vaccination among chronic myeloid leukaemia patients on tyrosine kinase inhibitors - Cheong, Chin Sum; Diana Ng, Leh Ching; Yap, Siew Hwei; Reena, Rajasuriar; Normala, Arshad; Nurul Syuhada, Zulhaimi; Kong, Boon Hong; Sam, I-Ching; Bee, Ping Chong; Jesinda Pauline, Kerishnan; Gan, Gin Gin (Academy of Medicine, Singapore., 2026)
Introduction: Chronic myeloid leukaemia (CML) patients on tyrosine kinase inhibitors (TKIs) show adequate antibody responses to SARS-CoV-2 vaccination, but T-cell responses remain unclear. This study investigates the overall immune responses in these patients after vaccination. Methods: In this longitudinal study, CML patients on TKIs who received at least 3 doses of the SARS-CoV-2 vaccine were assessed for neutralisation activity against the wild-type (WT) and Omicron variants at multiple timepoints: baseline (D0), week 4 (D28), month 6 (M6), and after the booster dose at months 3 (B3), 6 (B6), and 12 (B12). T-cell responses were evaluated at B6 and B12, with comparisons made to healthy controls (HC). Results: Twenty-seven CML patients and 113 HC were included. Neutralising activity against WT was similar across groups at all time points. Fewer CML patients exhibited positive neutralisation against Omicron at B6 (50.0% versus 88.9%, P=0.003), with higher antibody levels in CML patients at D28 and M6, but lower levels at B6 (P<0.05). T-cell responses were similar between groups at B6 and B12. Conclusion: Neutralising activity against WT and Omicron was similar, with a decline at B6, while T-cell responses were comparable across groups. These findings highlight the importance of continued vaccination in CML patients.